Power allocation method of battery energy storage system considering state balance in smoothing photovoltaic power fluctuations - Zhang, Jing; Hou, Lei; Diao, Xiaohong; Yang, Xin; Tang, Panpan; Cao, Xiaobo (Frontiers in Energy Research, 2022)
Aiming at the imbalances of SOC (state of charge, SOC) and SOH (state of health, SOH) for battery energy storage system (BESS) in smoothing photovoltaic power fluctuations, a power allocation method of BESS is proposed. Firstly, the hierarchical structure of the power allocation method is given, including acquisition of the grid-connected photovoltaic power reference and double-layer power allocation strategy for BESS. Secondly, a swing door trend algorithm optimized by the improved Aquila optimizer is devised and used to deal with the raw photovoltaic power to obtain the grid-connected signal. Next, the dynamic grouping principle considering the SOC and SOH of battery units is devised, and the double-layer power allocation method of BESS is designed in terms of the dynamic grouping results of battery units. Finally, the proposed power allocation method is simulated through actual data, and the results compared with other methods show that it can smooth photovoltaic power fluctuations more effectively, and the SOC and SOH can be balanced more quickly and accurately, which verifies its effectiveness.